Franco Evangelisti und die Improvisationsgruppe Nuova Consonanza: zum Phänomen Improvisation in der neuen Musik der sechziger Jahre - Gruppo di Improvvisazione Nuova Consonanza (Rome, Italy) (Milan Die Schachtel, 2006)
Il Gruppo was a brilliant and prolific composer's collective exploring extended techniques and new sound sources through the medium of improvisation. Although very much a product of its time, their music remains timeless. They were instrumental in founding a radical tradition of western musical improvisation that owed little or nothing to anybody and created some of the strangest music ever made. They were utterly unique.from John Zorn liner notes, NYC 2006This deluxe boxed edition presents some of the most compelling improvisations of this extraordinary improv group active in the 60s and featuring such names as Ennio Morricone, Ivan Vandor, Roland Kayn, Franco Evangelisti, Walter Branchi, Mario Bertoncini and John Heineman. Spanning from free-jazz to total abstract noise and wild electronic sounds, these pieces were recorded between 1967 and 1969 are released here for the first time. The enclosed video DVD, shot in a stunning black and white, is a unique document that captures the rehearsal of the thrilling concert that the group gave in Rome in 1967. It features both english and Italian subtitles. The cloth-covered box contains three individual digipak, a 72-pages italian-english booklet and a poster. Mastering by Giuseppe Ielasi